Effect of Saussurea costus extracts in the viability of Echinococcus granulosus protoscoleces of sheep origin In vitro - Asmaa Al-obaidy; Fouad Esmaeel (College of Education for Pure Sciences, 2021)
Cystic echinococcosis is one of the most prevalence and dangerous zoonotic parasitic disease in the world. Iraq is one of the most countries that affected by this disease. Surgery is usually the most effective therapy and can be used with injection of drugs in hydatid cysts before surgery to kill protoscoleces to avoid anaphylactic shock as a result of spilling of hydatid cyst fluid into peritoneal cavity, as well as this reduce the chance of secondary hydatid cysts production. Therefore, the current study  aimed  to evaluate the effectiveness of Saussurea costus extracts on protoscoleces viability of Echinococcus granulosus, where the protoscoleces of E. granulosus exposed to four different concentrations of Saussurea costus extracts at four different exposure times  including; 15, 30, 45 and 60 min in vitro, The results of ethanolic extract showed highest efficacy at concentration 20,30mg/ml in 45,60min and 40mg/ml at all times. The highest scolicidal effect of  petroleum ether extract was reported at 10 and 15mg/ml during 60min, while 20mg/ml reported similar effect at 45 and 60min. The data of cool aqueous extract showed reduction of protoscoleces viability to 0% at 200 and 250mg/ml in 45 and 60min, respectively, while 300mg/ml showed same reduction of viability at all experiment time periods.The data of hot aqueous extract showed 100% kill rate by using  350mg/ml at 60min and 400mg/ml at 45 and 60, as well as 450mg/ml at all experiment period times. Comparing to the control group. Generally, Saussurea costus extracts have concentration and exposure time-dependent effect on protoscoleces viability.